Inovasi Paving Block Bentuk Ikan Pari - Muhammad Rheza Fakhri Syakir; Raihan Dany Anantyo; Shifa Fauziyah; Riza Susanti (Universitas Diponegoro, 2024)
The weak interlock system in paving blocks can cause discomfort for drivers when passing over them. The more frequently traversed by vehicles, paving blocks with poor interlock systems will experience displacement. The compressive strength of paving blocks also affects their quality, thus supporting the performance of the paving block interlock system. This research aims to produce paving block products with a better interlocking system. The method used in this research is experimental and conducted in a laboratory setting. The results of the compressive strength test on stingray-shaped paving blocks, conducted at 14 days and converted to 28 days, showed superior compressive strength with an average of 24.04 MPa compared to conventional square and hexagonal paving blocks tested at 28 days, each with an average compressive strength of 20.07 MPa and 22.25 MPa, respectively. The water absorption test of the stingray-shaped paving blocks conducted at 7 and 14 days showed average water absorption rates of 5.67% and 4.31%, respectively, meeting the quality requirements of Grade B according to SNI -03-0691-1996, which requires less than 6%. Interlock system testing of the stingray-shaped paving blocks indicated superiority with an average displacement of 5.514 mm compared to conventional square and hexagonal paving blocks, each with an average displacement of 11.802 mm and 9.744 mm, respectively. The cost calculation for stingray-shaped paving blocks amounted to Rp. 2263.22 per paving block, 24,559% more economical than the total cost for conventional hexagonal paving blocks, which amounted to Rp. 3000.00.